Determining the effect of reinforcing a cement-concrete coating of bridges on the stressed-strained state of structures - Gameliak, Igor; Dmytrychenko, Andrew; Tsybulskyi, Vitalii; Kharchenko, Anna (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports a study of the cement-concrete coating on bridges using FRP reinforcement. That has made it possible to design optimal structures by selecting the height for reinforcement arrangement in the layers of a roadbed in order to ensure strength characteristics. An engineering method for calculating a hard roadbed with composite reinforcement has been devised, which makes it possible to take into consideration its work both in a joint package of the structure with a slab and separately – when it exfoliates from the slab of the bridge's span structure. Underlying this research are effort-determining methods, estimation dependences from the theory of bending layered structures, as well as dependences from elasticity theory to assess the strength of materials for a roadbed. The consideration of shear strains when designing slabs has helped establish that the deflections according to the devises method were 1.4 times larger than those in the classical approach. The method was tested by a numerical experiment, which confirmed the need to use composite reinforcement in the upper layers of a road surface on bridges, which improves its durability by 1.2 times. The results of the numerical experiment indicate that the equivalent stresses in the lower layers of a free-moving roadbed were 2.91 MPa, and, when operating in a joint assembly with a slab, they took a negative value (–0.2 MPa). Practical application of the devised calculation method makes it possible to determine the refined normal stresses in the layers of a roadbed, taking into consideration the characteristics of structure operation. Owing to this, additional opportunities open up for calculating the roadbeds of bridges whose design utilizes the most common types of span structures in the bridge industry.